Choroidal thickness in school children: the Gobi Desert Children Eye Study - Zhu, Dan; Jonas, Jost B. (PLOS ONE, 2017)
Purpose To investigate choroidal thickness (CT) and its associations in children in a school-based study. Methods The cross-sectional school-based Gobi Desert Children Eye Study included 1565 out of 1911 (81.9%) eligible children from all schools in the oasis region of Ejina in the Gobi Desert. A detailed ophthalmic examination was performed, including spectral-domain optical coherence tomography with enhanced depth imaging for CT measurement. Results CT measurements were available for 1463 (93.5%) students (mean age: 11.8±3.5 years; range:7-21 years). Mean subfoveal choroidal thickness (SFCT) was 282±49μm. CT was thickest at 1000μm temporal to the fovea (286±49μm), followed by the subfoveal region (282±49 μm; P<0.001), the region at 2500μm temporal to the fovea (278±49μm), the region at 1000μm nasal to the fovea (254±49μm;P<0.001), and the region at 2500μm nasal to the fovea (197±50μm;P<0.001). In cross-sectional analysis, the mean SFCT increased with age from 288μm at 7 years of age to 304μm at 11 years, and then decreased to 258 μm at 18 years. In multivariate analysis, thicker SFCT was associated (regression coefficient r:0.38) with higher hyperopic refractive error (P<0.001;standardized regression coefficient beta:0.31;non-standardized regression coefficient B:7.61;95% confidence intervals (CI):6.29,8.93), younger age (P<0.001;beta:-0.10;B:-1.39;95%CI:-2.14,-0.64), male gender (P = 0.03;beta:-0.05;B:-5.33;95%CI:-10.1,-0.53), higher corneal refractive power (P<0.001;beta:0.12;B:3.68;95%CI:2.12,5.24), and non-Han Chinese ethnicity (P = 0.03;beta:0.05;B:6.16;95%CI:0.50,11.8). Ratio of CT(1000μm nasal to fovea)/SFCT (0.90±0.06;range:0.66,1.23) and ratio of CT(2500μm nasal to fovea)/SFCT (0.70±0.13;range:0.28,1.23) decreased with older age (P = 0.01;and P = 0.001, respectively), while ratio of CT(1000μm temporal to fovea)/SFCT (1.02±0.06;range:0.56,1.37) and ratio of CT(2500μm temporal to fovea)/SFCT (0.99±0.11;range:0.54,1.84) increased with older age (both P<0.001). Time spent outdoors or indoors was not significantly associated with CT-related parameter in multivariate analysis. Conclusions In contrast to SFCT in adults and despite elongating axial length, SFCT in children increased in cross-sectional analysis with older age (up to 11 years of age) and then started to decrease with further ageing. It suggests an increase in choroidal volume up to the age of 11 years. In children, the choroid was thickest at 1000μm temporal to the fovea, followed by the subfoveal region, and this difference significantly increased with older age. In contrast, CT nasal to the fovea in relationship to SFCT decreased with older age. CT was independent of lifestyle-associated parameters.